Investigating Banking Profitability: Evidence from Commercial Banks in Emerging Country - Irhamni, Firly (Universitas Nahdlatul Ulama Surabaya, 2022)
We empirically analyse the determinants of commercial banking profitability in Indonesia for the period 2014-2018. We contribute to the growing literature in practical ways, first we propose suggestion to the business of the commercial banking sector in Indonesia, especially in decision-making of financial condition, in order to maximize the performance of the company and shareholders, so that the banking company's shares can continue to survive and have large returns. Also, it is expected to provide insight and knowledge about the extent to which the relationship between the banking sound’s level variable and its Profitability. The sample in this study amounted to 17 banking companies. This study uses purposive sampling method and we apply multiple linear regression approach with SPSS. We found that credit portfolio quality has a negative and significant effect on profitability, bank solvency has a positive and significant effect on profitability, interest level has a positive and insignificant effect on profitability. Efficiency ratio has a negative and insignificant effect on profitability, and liquidity has a positive and insignificant effect on profitability. Keywords: bank profitability, emerging economy, credit quality, solvency, interest margin, efficiency